ON THE DETERMINATION OF GALAXY STRUCTURE ELLIPTICITY - Biernacka, M.; Flin, P.; Juszczyk, T.; Panko, E. (Одеські астрономічні публікації, 2007)
We discuss factors influencing the determination of the observed shape of galaxy clusters when the covariance ellipse method is involved. The analysis of 377 Abell clusters show that at greater distances from the cluster center the ellipticity is rather smooth. There were no statistical differences among ellipticities when the cluster center was located at the brightest cluster member, the third brightest galaxy, the mean as well as the median values of galaxy coordinates. Moreover, we show that for rich galaxy clusters the distribution of ellipticities is the same for two totally different cluster samples.